FKBP5 Exacerbates Impairments in Cerebral Ischemic Stroke by Inducing Autophagy via the AKT/FOXO3 Pathway - Yu, Shijia; Yu, Mingjun; Bu, Zhongqi; He, Pingping; Feng, Juan (Frontiers in Cellular Neuroscience, 2020)
Cerebral ischemic stroke is regarded as one of the most serious diseases in human central nervous system. The secondary ischemia and reperfusion (I/R) injury increased the difficulty of treatment. Moreover, the latent molecular regulating mechanism in I/R injury is still unclear. Based on our previous clinical study, we discovered that FK506 binding protein 5 (FKBP5) is significantly upregulated in patients, who suffered acute ischemic stroke, with high diagnostic value. Levels of FKBP5 were positively correlated with patients’ neurological impairments. Furthermore, a transient middle cerebral artery occlusion (tMCAO) model of mice was used to confirm that FKBP5 expression in plasma could reflect its relative level in brain tissue. Thus, we hypothesized that FKBP5 participated in the regulation of cerebral I/R injury. In order to explore the possible roles FKBP5 acted, the oxygen and glucose deprivation and re‐oxygenation (OGD/R) model was established to mimic I/R injury in vitro. FKBP5 expressing levels were changed by plasmids stable transfection. The altered expression of FKBP5 influenced cell viability and autophagy after OGD/R injury notably. Besides, AKT/FOXO3 cascade was involved in FKBP5 regulating process. In the present study, FKBP5 was verified upregulated in cerebral I/R injury, related to the severity of ischemia and reperfusion injury. Additionally, our analyses revealed that FKBP5 regulates autophagy induced by OGD/R via the downstream AKT/FOXO3 signaling pathway. Our findings provide a novel biomarker for the early diagnosis of ischemic stroke and a potential strategy for treatment.